2018
DOI: 10.1016/j.eururo.2017.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Mannitol Versus Placebo During Partial Nephrectomy in Patients with Normal Kidney Function: A Double-blind, Clinically-integrated, Randomized Trial

Abstract: In this randomized trial, patients with normal kidney function who received mannitol during surgery to remove part of their kidney had no better kidney function 6 mo after surgery than those who did not receive mannitol. We conclude that this routine practice should be discontinued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…A number of clinical studies have examined the utility of mannitol during PN, including a phase 3, double-blind randomized control trial of 199 patients with estimated GFR (eGFR) > 45 ml/min/1.73 m 2 who underwent PN and were randomized to receive intravenous mannitol or saline placebo at the time of surgery. At 6 wk and 6 mo, renal function outcomes in either group were similar, showing no significant difference [32]. These results were replicated in a single-surgeon randomized control trial of robotic PN of 79 patients using 12 g mannitol [33].…”
Section: Renal Function Preservation In Pnmentioning
confidence: 67%
“…A number of clinical studies have examined the utility of mannitol during PN, including a phase 3, double-blind randomized control trial of 199 patients with estimated GFR (eGFR) > 45 ml/min/1.73 m 2 who underwent PN and were randomized to receive intravenous mannitol or saline placebo at the time of surgery. At 6 wk and 6 mo, renal function outcomes in either group were similar, showing no significant difference [32]. These results were replicated in a single-surgeon randomized control trial of robotic PN of 79 patients using 12 g mannitol [33].…”
Section: Renal Function Preservation In Pnmentioning
confidence: 67%
“…45 A recent RCT by Spaliviero et al studied potential effects of mannitol in nephron sparing surgery in 199 patients with a pre-operative estimated GFR (eGFR) > 45 mL/min/1.73 m 2 . 46 The authors identified no significant differences in eGFR at six weeks or six months, or on renal radionuclear scintigraphy scans at six months. In 65 patients who underwent robotic assisted laparoscopic partial nephrectomy (RALPN), Choi et al observed no difference between individuals receiving 12 g mannitol vs. controls.…”
Section: Mannitol In Renal Surgerymentioning
confidence: 90%
“…In respective studies and the trial by Spaliviero et al, kidney hypothermia was at least partly used as an additional renoprotective measure, primarily in controls. 31,32,46 Mannitol in liver surgery Wahbah et al evaluated different combinations of dopamine and mannitol vs. controls in obstructive jaundice. 50 No differences in any of the chosen end points were noted.…”
Section: Mannitol In Renal Surgerymentioning
confidence: 99%
“…A recent investigation of another flawed concept concluded that administration of mannitol infusion, which was considered to be another factor during NSS, had no significant impact on kidney function as assessed at 6 mo after surgery [10].…”
Section: Evidence Synthesismentioning
confidence: 99%